Landscape analysis of urban growth patterns in Seremban, Malaysia, using spatio-temporal data - Aburas, Maher Milad; Abdullah, Sabrina Ho; Ramli, Mohammad Firuz; Ashaari, Zulfa Hanan (2016)
Urban growth is one of the major issues that have played a significant role in destroying the ecosystem in recent years. Landscape analysis is an important technique widely used to evaluate urban growth patterns. In this study, four land-use maps from 1984, 1990, 2000, and 2010 have been used to analyze an urban landscape. The values of a built-up area were initially computed using a geographic information system environment based on the spatial gradient approach. Mathematical matrices were then used to determine the amount of change in urban patches in each direction. Results of the number of patches, landscape shape index, aggregation index, and total edges confirmed that the urban patches in Seremban, Malaysia, have become more dispersed from 2000 to 2010. The urban patches have also become more continuous, especially in the north-western part of Seremban as a result of the urban development in the Nilai District. These results indicate the necessity to create new policies in the city to protect the sustainability of the land use of Seremban.